Plant cells formed their protective structures use molecules of phytopathogenic microorganisms - Emelyanov, V.I.; Polyakovskiy, S.A.; Sakada, V.I.; Grodzinskiy, D.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
During pathogenesis, plant cells are capable to forming their own structures at the expense of the molecules, which were a part of fungi cell walls. Autoradiographic analysis showed the presence of 14C-glucose in cells of onion, which were recently the compounds of the cell walls Botrytis senerea. Radioisotope method confirmed the presence of labeled glucose in Allium cera cells, the protective poly-β-1,3-glucose – callose.